PEWUJUDAN DAN PENYERAPAN PEMAIN DALAM VIDEO GAME - Yuwono, Ardian Indro; Simatupang, Gabriel Roosmargo Lono Lastoro; Salam, Aprinus (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2018)
In playing various video game, gamers unconsciously and automaticly embodied theirself inside the video game. The embodiment process are portrayed through icons, avatars and mostly their in-game characters, while the immersion happens during the process of playing, which can occur inside and outside of the video game. The playing intensity and the amount of time spend in playing video game determine the overall process of embodiment and immersion, beside the player sociocultural condition. This research uses ethnography to identify how gamers play the video game to fulfill their intrinsic needs such as competence, autonomy and relatedness. To cite this article (7th APA Style): Yuwono, A. I., Simatupang, G. R. L. L. & Salam, A. (2018). Pewujudan dan penyerapan Pemain dalam Video Game [Embodiment and Immersion of Players in the Game Video]. Journal Communication Spectrum, 8(1), 94-112. http://dx.doi.org/10.36782/jcs.v8i1.1837